Tiktok Media in Purchase Decision: The Effect of User Generated Content (UGC), Brand Equity, and Digital Marketing on Skincare Product - Andriansyah; Kharisma Fitri Rahmawati; May Dedu; Agustina (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
This study focuses on determining how much influence User Generated Content (UGC), Brand Equity, and Digital Marketing have on Purchase Decisions. This research is motivated by using the Tiktok platform as a Digital Marketing medium that influences Purchase Decisions, especially on skincare products. The phenomenon of user generated content (UGC) on Tiktok has created a new paradigm in digital marketing strategies and the formation of brand equity. This research methodology is quantitative, with a survey approach to 235 respondents aged 18-36 years who have purchased skincare products based on content on Tiktok. Data was collected through online questionnaires with purposive sampling techniques and analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS); each association between variables has a p-value less than 0.05. This finding shows that user generated content (UGC), brand equity, and digital marketing significantly affect the purchase decision of skincare products. These findings also provide important implications for skincare companies in optimizing digital marketing strategies through the Tiktok platform.